Benefits of Early Mobilization After Pediatric Liver Transplantation*. Issue 2 (February 2019) - Tsuboi, Norihiko; Hiratsuka, Miku; Kaneko, Setsushi; Nishimura, Nao; Nakagawa, Satoshi; Kasahara, Mureo; Kamikubo, Takeshi
Abstract : Objective: To evaluate the impact of early mobilization after pediatric liver transplantation in the PICU. Design: A 70-month retrospective before-after study. Setting: Medical and surgical PICU with 20 beds at a tertiary children's hospital. Patients: Seventy-five patients 2–18 years old who underwent liver transplantation and could walk before surgery. Intervention: We meticulously planned and implemented an early mobilization intervention, a multifaceted framework for early mobilization practice in the PICU focusing on a multidisciplinary team approach. Measurements and Main Results: There was a significant increase in the proportion of patients who received physical therapy in the PICU (66% vs 100%; p < 0.001), especially within the first 48 hours after transplantation (9% vs 78%; p < 0.001). Furthermore, the time spent for physical therapy per eligible patient and per eligible PICU day increased (8.1 min [interquartile range, 0–10.6 min] vs 17.4 min [13.2–26.6 min]; p < 0.001). Compared with patients in the pre-early mobilization period, patients in the post-early mobilization period were able to walk again for more than 50 yards without a rolling walker earlier (28 [16–66] vs 23 [19–31] postoperative days; p = 0.015 by the Gray test), and the length of hospital stay of the post-early mobilization group was shorter than that of the pre-early mobilization group (55 [37–99] vs 40 [31–54] postoperative days; p = 0.012). Conclusions: Through implementation of early mobilization for pediatric patients who underwent liver transplantation, the duration from liver transplantation to regaining the ability to walk again without a rolling walker became shorter. Early mobilization intervention was beneficial for pediatric patients who underwent liver transplantation and could walk before surgery.